Gallaudet encyclopedia of deaf people and deafness - Van Cleve, John V.; Gallaudet College (New York : McGraw-Hill, 1987)
Contains 273 entries to information derived from the sciences, the social sciences, and the humanities. Comprehensive coverage, including biographical, subject, and historical information. Many entries contain sub-topics. Articles are signed and include references. Index in last volume.
Includes bibliographies and index.
Keywords: Deafness; Encyclopedias